Impact Of Psychological Skill Training On Sporting Performance Of University Level Football Players - Babar Kamil , Akhtar Nawaz Ganjera (Migration Letters, 2022)
This study investigates the impact of Psychological Skill Training (PST) on the sporting performance of university-level football players. The study employed an experimental research design with pre- and post-tests involving two groups: an experimental group (n=16) that received PST and a control group (n=16) that did not. Thirty-two football players aged 20-25 years from Forman Christian College, Lahore, participated. The participants were assessed using the Sports-related Mental Toughness Questionnaire (SMTQ), Automatic Self-Talk Questionnaire (ASTQ), Sport Imagery Ability Questionnaire (SIAQ), Perception of Success Questionnaire (PSQ), and Sport Motivation Scale (SMS). PST was delivered in three phases: education, acquisition, [1]and implementation, focusing on relaxation, imagery, and self-talk techniques. Data analysis, conducted using SPSS (23.0), included correlation and regression analyses to examine the relationships and effects of PST on the players’ mental toughness, perception of success, motivation, and overall sports performance. The results revealed that PST had a significant positive impact on all assessed variables. Regression analysis showed that PST was a strong predictor of mental toughness (β = 0.595, p < 0.001), perception of success (β = 0.732, p < 0.001), motivation (β = 0.773, p < 0.001), and sports performance (β = 0.563, p = 0.001). These findings suggest that PST can effectively enhance the psychological attributes and athletic performance of football players, emphasizing its potential as a valuable tool in sports training programs. The study underscores the importance of integrating psychological skills into sports training to optimize athletes’ performance.